William Blake and the Music of the Songs - Hutchings, Kevin (Romanticism on the Net, 2007)
AbstractAlthough Blake combined the “sister arts” of poetry, painting, and music in much of his early illuminated work, scholars have (with a few exceptions) rarely considered the musical aspect of his multi-media practice in detail. This tendency to “forget” about Blake’s musical artistry is entirely understandable, because the melodies that Blake wrote for many of his early poems did not survive his death in 1827. Building upon B. H. Fairchild’s groundbreaking work in Such Holy Song (1980), this multi-media essay examines Blake’s musical practice in relation to the poetry and designs of Songs of Innocence and of Experience. Beginning with a biographical discussion of Blake’s musicianship, the essay considers the role music played as an integral and holistic aspect of Blake’s “composite art.” Subsequently, the essay addresses some of the interpretive challenges facing modern composers who attempt to set Blake’s poetry to music; and it explores some of the ways in which music can inform modern pedagogy of the Songs. In an appendix, the essay places Blake’s verbal and visual media into a musical context by providing access to relevant MP3 music files taken from Kevin Hutchings’ CD Songs of William Blake (2007).